Multiple methods of diet assessment reveal differences in Atlantic puffin diet between ages, breeding stages, and years - Kennerley, William L.; Clucas, Gemma V.; Lyons, Donald E. (Frontiers in Marine Science, 2024)
Atlantic puffin (Fratercula arctica, hereafter "puffin") reproductive success in the Gulf of Maine (GoM) has decreased following a recent oceanographic regime shift and subsequent rapid warming. Concurrent changes in both the regional forage fish community and puffin chick diets and provisioning rates suggest that inadequate prey resources may be driving this decline. To determine what prey GoM puffins were feeding on during two years of marine heatwave conditions, we assessed puffin diet simultaneously using two methods: traditional, observational methods that utilize bill-load photography and emerging methods employing fecal DNA metabarcoding. We identified a strong correlation between the composition of chick diet as estimated through traditional and emerging methods, supporting the interpretation of DNA relative read abundance as a quantitative metric of diet composition. Both methods identified the same dominant prey groups but metabarcoding identified a greater number of species and offered higher taxonomic resolution. Puffin adults and chicks fed on many of the same prey types, although adults consumed a greater variety of taxa and consumed more low quality prey than they provisioned chicks, as predicted by optimal foraging theory. For both age classes, diet varied both between and within years, likely reflecting changes in the local forage fish community in response to environmental variability. During these two years of marine heatwave conditions, puffins exploited unusual abundances of typically-uncommon prey, yet low puffin productivity suggests the observed dietary plasticity was not able to compensate for apparent prey shortages. Continued refinement of molecular methods and the interpretation of the data they provide will enable better assessments of how seabirds of diverse ages and breeding stages are compensating for changing forage fish communities driven by global climate change.